Developing common values in situations of plurality and social transformation - Lategan, Bernard (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Social transformation is always accompanied by a change in basic values. When this occurs in situations with high levels of diversity, it is important for the eventual success of the transition that there is sufficient agreement on what the basic value system of the new dispensation should be. The article discusses the role of foundational documents like the Freedom Charter and the South African Constitution during the transition to an inclusive democracy in South Africa and the challenge to implement the values contained in these documents in various contexts in society. As a case study, the process to develop a set of common values in a major gold mine and the practical implementation of these values in the workplace is analysed. It is concluded that – like the publics of the academy and of the church need a dedicated style of discourse for successful communication with these publics – discourse in the context of general society also needs a specific style of discourse. This discourse must be inclusive and generic and therefore not religion-specific. Features of this style of discourse are illustrated at the hand of examples from the case study.